Porous borders: The study of illegal markets from a sociological perspective - Matías Dewey (Max Planck Institute for the Study of Societies, 2016)
State concerns about crime and security issues have strongly affected conceptions of economic action outside the law, a traditional field of research in sociology. This increasing encroachment by policy-related concerns on the intellectual framework of the discipline has led, on one hand, to an almost exclusive focus on criminal organizations in the analyses of illegal economic activity. On the other hand, it has led to the downplaying of the importance of classic topics of sociological reflection, such as the embeddedness of action, the moral dimension of illegal products, or the relationship between social change and the spread of illegal exchanges. This short paper problematizes economic action outside the law by taking legal definitions and their effects seriously. It begins with the problem of naturalizing state definitions. This is followed by a discussion of the illegality of illegal markets, which illustrates sociological contributions. Finally, three dimensions of the study of illegal markets are suggested. Overall, the paper lays out a research program for this field of sociological inquiry. – – Das staatliche Interesse an Kriminalitäts- und Sicherheitsfragen wirkt sich massiv auf das Verständnis von illegalen ökonomischen Handlungen aus, einem klassischen soziologischen Forschungsgebiet. Der zunehmende Eingriff in die intellektuelle Struktur der Disziplin hat zur Folge, dass der Fokus fast ausschließlich auf die Analyse illegalen Markttauschs gerichtet ist und die Bedeutung klassischer soziologischer Themenfelder - wie die Einbettung wirtschaftlichen Handelns, die moralische Dimension illegaler Güter oder die Verbindung zwischen sozialem Wandel und der Verbreitung illegaler Märkte - heruntergespielt wird. Dieses kurze Paper diskutiert illegale ökonomische Handlungen, indem es Legaldefinitionen und ihre Auswirkungen ernst nimmt. In einem ersten Schritt beschreibt es das Problem naturalisierender staatlicher Definitionen. In einem zweiten Schritt diskutiert das Papier die Illegalität illegaler Märkte, womit soziologische Beiträge illustriert werden. Schließlich werden drei Dimensionen für die Analyse illegaler Märkte vorgestellt. Insgesamt skizziert das Paper ein Forschungsprogramm für diesen Bereich soziologischer Analyse.
Keywords: 300